Comparative Analysis of Conventional Rotary Drilling and Reverse Circulation Drilling Methods in Bored Pile Construction - Mohamad Amir Izaril; Muhamad Faiz (Progress in Engineering Application and Technology, 2025)
The ECRL is a strategic rail link project to enhance rail network across Peninsular Malaysia.The key part of the project includes construction of Temporary Bridge (TB30) across Sungai Klang at chainage CH70+240, in the state of Selangor, which is required for supporting bored piling works for permanent structures. However, conventional rotary drilling (CRD) equipment cannot be used under the bridge with a load restriction of 90 tons, and hence RCD equipment has been adopted as the lightweight alternative. To the best of knowledge, a comparison between RCD and CRD is taken out based on the restrictions of temporary bridge. Performance indicators, such as ROP, drilling efficiency, and pile integrity were taken into consideration to determine the general adequacy of the drills. To evaluate both drilling methods, this study used on-site data, direct observations, and performance comparisons. The findings showed that while Reverse Circulation Drilling (RCD) can handle the required structural loads and is more efficient in terms of mobility and fuel use, it does face some challenges in waterlogged riverbed soils, where proper calibration is crucial to ensure good pile quality. In the end, the research recommends the most suitable method for bored piling based on site-specific conditions, highlighting key factors like safety, cost, and long-term durability. This work aims to support better engineering decisions for temporary bridge construction and similar infrastructure projects in the future